2011
DOI: 10.1186/1752-1947-5-459
|View full text |Cite
|
Sign up to set email alerts
|

Two successful natural pregnancies in a patient with severe uterine prolapse: A case report

Abstract: IntroductionUterine prolapse is a common gynecologic condition that is rare during or before pregnancy. We report an exceptional case of two pregnancies in a totally prolapsed uterus.Case presentationA 36-year-old Caucasian woman with a history of uterine prolapse presented with pregnancy. A vaginal pessary was applied to keep her uterus inside the pelvis after manual reposition. The pessary was removed at the 24th week. The gravid uterus persisted in the abdominal cavity because of its increased volume.Conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 5 publications
0
39
0
1
Order By: Relevance
“…Primary vaginal cancer is not common, representing 1-2% of all genital malignancies in women [1]. Reviewing the literature on uterine prolapse reported before 1970, we found that most cases of uterine prolapse are located in economically undeveloped areas, where grand multiparity is more common [2]. We present this rare case of severe uterine prolapse complicated by primary vaginal cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Primary vaginal cancer is not common, representing 1-2% of all genital malignancies in women [1]. Reviewing the literature on uterine prolapse reported before 1970, we found that most cases of uterine prolapse are located in economically undeveloped areas, where grand multiparity is more common [2]. We present this rare case of severe uterine prolapse complicated by primary vaginal cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies had shown that prolapse is more common in women who had given birth than nulliparous women. 9 In this study, it is dominated by unemployed women, as many as 188 women while women who work were 70 patients. Patients had low economy status with heavy domestic workloads.…”
Section: Resultsmentioning
confidence: 73%
“…Having more than one vaginal birth and the use of forceps or vacuum during prolonged labour are the important risk factors for prolapse. Other predisposing factors include obesity, connective tissue disease, chronic coughing, ethnic origin and family history (3,4). In our case, the prolapse occurred soon after delivery of her first baby and persisted during the subsequent pregnancies.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, obstructed labour and uterine rupture due to prolonged labour related to the prolapse remain serious and life-threatening intrapartum complications (6,7). Although the mode of delivery is controversial in cases of uterine prolapse, caesarean section is recommended as the safest option to prevent potentially dangerous intrapartum complications, such as obstructed labour and uterine rupture (3,(8)(9)(10). Management of a uterine prolapse concurrent with pregnancy consists of bed rest in a slight Trendelenburg position and the usage of pessary.…”
Section: Discussionmentioning
confidence: 99%